Low tension breast hydatid cyst-A case report - Maulana M. Ansari; Shahla Haleem; Wasif M. Ali; Leonard J. Enzung; Sheikh S. Ali; Sunder K. Meet (Elsevier, 2014)
Summary: Introduction: Features of low tension in breast hydatid cyst and symptoms secondary to cyst dying and disintegration are unique and not yet reported in the literature. Material and method: An young woman of 30 years complained about pain and vague swelling in the right breast during follow-up with albendazole therapy following second laparotomy for post-surgical residual cavity of hydatid cyst in the left lobe of the liver. Breast ultrasound was diagnostic. Results: Segmental breast excision revealed a large dead hydatid cyst. Postoperative course was uneventful. Conclusions: Breast hydatid cyst may become symptomatic and hypotensive after start of albendazole therapy. Keywords: Breast hydatid, Hydatid cyst, Echinococcus, E. granulosus, Albendazole, Dead hydatid cyst